Mendelian randomization analysis identified tumor necrosis factor as being associated with severe COVID-19 - Song, Hongfei; Lei, Na; Zeng, Ling; Li, Xiuyan; Jiang, Cen; Feng, Quansheng; Su, Yue; Liu, Jibin; Mu, Jie (Frontiers in Pharmacology, 2023)
Background: Observational studies have shown that anti-tumor necrosis factors (TNF) therapy may be beneficial for patients with coronavirus disease 2019 (COVID-19). Nevertheless, due to the methodological limitations of traditional observational studies, it is difficult to make causal inferences. Here, we performed a two-sample Mendelian randomization analysis to investigate the causal link between 9 TNFs and COVID-19 severity using publicly available genome-wide association study (GWAS) summary statistics. Methods: Summary statistics for 9 TNFs (21,758 cases) were obtained from a large-scale GWAS. Data on the associations between single nucleotide polymorphisms (SNPs) and severe COVID-19 (18,152 cases vs. 1,145,546 controls) were collected from the COVID-19 host genetics initiative. The causal estimate was calculated by inverse variance weighted (IVW), MR Egger and weighted median approaches. We also conducted additional sensitivity tests to assess the validity of the causal relationship. Results: Genetically predicted tumor necrosis factor receptor superfamily member 6 (FAS) was positively causally associated with the severity of COVID-19 (IVW, odds ratios (ORs)=1.10, 95% confidence interval (CI)=1.01-1.19, P=0.026) and tumor necrosis factor receptor superfamily member 5 (CD40) was protective against severe COVID-19 (IVW, OR=0.92, 95% CI=0.87-0.97, P=0.002). Conclusion: Genetic evidence from this study supported that increased expression of FAS was associated with the risk of severe COVID-19 and that CD40 may have great potential for COVID-19 in terms of vaccine development.